Profile of Esophageal Cancer Management - Saskia Andiani; Rizka Fathoni Perdana; Budi Widodo; Puguh Setyo Nugroho (GLOBAL HEALTH SCIENCE GROUP, 2026)
Esophageal cancer is one of the leading causes of cancer-related mortality worldwide, often diagnosed at an advanced stage with limited therapeutic options. In Indonesia, particularly at Dr. Soetomo General Hospital Surabaya, data regarding esophageal cancer treatment remain limited. A better understanding of treatment profiles and patient characteristics is essential to improve clinical outcomes and develop early detection strategies. To analyze the profile of esophageal cancer treatment at Dr. Soetomo General Hospital Surabaya during 2018–2023, including patient demographics, clinical manifestations, nutritional status, histopathological and anatomical characteristics of the tumor, TNM stage, metastasis, comorbidities, therapeutic modalities, serum albumin levels, and prognosis. This was a descriptive retrospective study using secondary data obtained from medical records of esophageal cancer patients at the Oncology Clinics of ENT-HN and Internal Medicine Departments, Dr. Soetomo General Hospital, from 2018 to 2023. Total sampling was applied, with 65 patients meeting the inclusion criteria out of 157 cases. Data analyzed included demographic characteristics, clinical symptoms, nutritional status, tumor type and location, TNM stage, presence of metastasis, comorbidities, therapy received, serum albumin levels, and treatment outcomes. The data were analyzed descriptively and presented as frequency distributions. The majority of patients were male and aged ≥60 years, presenting with dysphagia as the most common symptom. Most patients were diagnosed at advanced stages, with squamous cell carcinoma as the predominant histological type and the distal third of the esophagus as the most frequent tumor location. Common comorbidities included hypertension and diabetes mellitus. Many patients had hypoalbuminemia, reflecting poor nutritional status. Therapeutic modalities provided included gastrostomy, chemotherapy, radiotherapy, or their combination, although a substantial proportion received only supportive care. Mortality remained high, and curative outcomes were limited. Esophageal cancer cases at Dr. Soetomo General Hospital were predominantly diagnosed at advanced stages with poor nutritional status and multiple comorbidities, resulting in limited curative treatment options and poor prognosis. Strengthening early detection, nutritional optimization, and multidisciplinary care are crucial to improving outcomes in esophageal cancer patients.